Concevoir des logements collectifs en bois : un processus à l’épreuve de la technique - Mathilde Planchot; Céline Drozd; Ignacio Requena-Ruiz; Daniel Siret (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Collective housing using bio-sourced materials is currently undergoing a phase of research and experimentation that involves the various players in complex projects. While this approach is not new, it does provide a field for observing the transformations at work in the design processes impacted by environmental issues. The use of timber seems to place the subject of technique back at the heart of a program whose automatisms induced by decades of reinforced concrete envelope implementation are being turned upside down. In this article, we ask to what extent the use of timber in collective housing implies a level of technicality that transforms and renews the process of collective housing design. To shed some light on these issues we report on the results of a survey conducted in the form of interviews with eight architects designing timber collective housing, who analyze their practices and the transformations they observe.